Komparasi Karakteristik Menara Pendingin Menggunakan Beberapa Tipe Susunan Pipa-pipa sebagai Pendistribusi Cairan - Susanto Johanes (Forum Teknik, 2011)
The aims of the experiments are to characterize of the cooling tower by using the bank of the pipes as the fluid distributor. The cooling tower is constructed by rectangle of glasses which it has 9 cm x 9 cm in cross section and 100 cm in height. The fluid distributors are constructed by pipes in 5/8 inch of nominal diameter. There were five types of the packing namely the fluid distributor without baffle, fluid distributor with one baffle, the fuid distributor with two baffles, the fluid distributor with there baffles and the fluid distributor with four baffles.     The experiment have been done by flowing the hot water from the top of cooling tower through the fuid distributor, on the other hand, the air cooler is flown above through the fluid distributor opposite to the water flow direction. This process makes the exchanging of the heat between air and water on the fluid distributor. The variables varied in this experiments are the inlet water temperature, Twi (45, 50, 55 and 60 °C), the height of fluid distributor, Z (30.5, 61 and 91.5 mm), the ratio of water/air mass flow, mw/ma (3.624, 5.888 and 7.700) and the number of baffle (without baffle,  one baffle, two baffles, three baffles and four baffles).     The experimental results show that in the ratio of water/air mass flow rate which is lower, the increasing of the numbers baffle cause the decreasing of characteristic. Mean while, in the ratio of water/air mass flow rate which is higer, the increasing of the numbers of baffle cause the increasing of the characteristic. The cooling tower without the fluid distributor has the average characteristic is 13.4% and the average effectiveness is 16.2%. For the cooling tower with the fluid distributor has the average characteristic is 31.5% and the average effectiveness is 25.0%. Keywords : Cooing tower,  characteristic, fluid distributor.